Designed borophene/TMDs hybrid catalysts for enhanced hydrogen evolution reactions. Issue 44 (28th October 2021) - Lin, Yuxing; Yu, Mingxin; Li, Xiaoyan; Gao, Weicheng; Wang, Licheng; Zhao, Xinli; Zhou, Min; Yao, Xiaojing; He, Maoshuai; Zhang, Xiuyun
Abstract : Interlayer charge transfer in borophene/TMDs heterostructures plays an important role in tuning electronic properties, which on one hand, can effectively improve the HER performance of TMDs basal plane and on the other, can maintain the good HER performance of botophene layer. Abstract : Interlayer charge transfer in heterostructures plays an important role in tuning electronic properties, which opens a new avenue for potential applications of two-dimensional nanomaterials. In this work, the hydrogen evolution reaction (HER) performance of borophene/TMDs heterostructures is systematically explored by using density functional theory calculations. The HER performance of these heterostructures is superior to that of the pure TMDs due to the interlayer charge transfer. In contrast, the perfect HER performance of the borophene layer is well contained. Particularly, borophene/VS2 s display good HER performance on both sides. These results shed more light on designing excellent electrochemical HER catalysts at the nanoscale.